The Characteristics of Wet Noodles from Mocaf Flour and Moringa Flour - Amir Hinggiranja; Ni Made Ayu Suardani Singapurwa; I Gede Pasek Mangku; I Putu Candra; A.A. Made Semariyani (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of substituting mocaf flour for moringa leaf flour on the characteristics of wet noodles. The research method used a completely randomized design on a factorial pattern, namely the ratio of wheat flour to mocaf flour, consisting of 4 levels: (100:0), (90:10), (80:20), (70:30), and the addition of moringa leaf flour, which consists of three levels: (10%), (15%), and (20%). The results showed that the best substitution of mocaf flour and moringa leaf flour with a ratio of 70% wheat flour to 30% mocaf flour and leaf flour to 10% moringa yielded 71.467% moisture content and 13.249% protein content. Ash content of 1.359% does not meet SNI but is still accepted by consumers. swelling index 32.723%, color (L*) 39.580%, color (a*) -8.380%, and color (b*) 14.410%.